Theoretical assessment of the effectiveness of application single-stage long-stroke piston compressors in refrigeration and hydrocarbon gas liquefaction systems - V. L. Yusha (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The analysis of the main modern technologies for obtaining low temperatures and liquefying hydrocarbons using compressor equipment is presented and the most significant results of research in the field of low-flow compressors based on low-speed, long-stroke piston stages are presented. A method for calculating an ideal vapor-compression refrigeration cycle is presented, adapted to the object under consideration, taking into account the possibility of implementing quasi-isothermal compression. A comparative computational analysis of temperature conditions and thermodynamic efficiency of a two-stage refrigeration cycle and single-stage refrigeration cycles is carried out during adiabatic and quasi-isothermal compression processes in the boiling temperature range 278 K ... 198 K. It is shown that in terms of the discharge temperature and coefficient of performance, a single-stage vaporcompression ammonia refrigeration machine based on a low-speed quasi-isothermal stage is comparable to a similar two-stage machine based on adiabatic stages. This allows, in relation to actual objects — small refrigeration machines and installations, to predict both the energy and technical advantages of using a single-stage scheme based on low-speed, long-stroke piston compressors. In addition, it has been shown that the effective use of such a compressor is also possible in hydrocarbon liquefaction systems, while ensuring their safe temperature conditions in a wide range of atmospheric temperatures.